THE RESPIRATORY RATE OF THE SCIATIC NERVE OF THE FROG IN REST AND ACTIVITY - Moore, A. R. (The Rockefeller University Press, 1919)
1. With the indicator method of Haas, the rates of carbon dioxide production have been measured in the case of the sciatic nerve, various parts of the brain, and the sartorius muscle of the frog. The rate of respiration of the sciatic nerve is from 10 to 30 per cent of that of the other tissues, varying somewhat with the individual. 2. Stimulation of the sciatic nerve with induction shocks sufficient to induce tetanus of the muscle does not increase the output of carbon dioxide from the sciatic nerve, even if continued as long as 30 minutes. Sartorius muscle used as a control showed a marked increase in carbon dioxide production upon relaxation after contraction resulting from such stimulation. 3. These facts indicate that the nerve impulse does not depend upon processes leading to the production of carbon dioxide.